Healing process of dog dental pulp after pulpotomy and pulp covering with mineral trioxide aggregate or Portland cement. - Holland, Roberto [UNESP]; Souza, Valdir de [UNESP]; Murata, S. S.; Nery, Mauro Juvenal [UNESP]; Bernabé, Pedro Felício Estrada [UNESP]; Otoboni Filho, José Arlindo [UNESP]; Dezan Junior, Eloi [UNESP] (My University, 2001)
Considering several reports about the similarity between the chemical compositions of the mineral trioxide aggregate (MTA) and Portland cement (PC), the subject of this investigation was to analyze the behavior of dog dental pulp after pulpotomy and direct pulp protection with these materials. After pulpotomy, the pulp stumps of 26 roots of dog teeth were protected with MTA or PC. Sixty days after treatment, the animal was sacrificed and the specimens removed and prepared for histomorphological analysis. There was a complete tubular hard tissue bridge in almost all specimens. In conclusion, MTA and PC show similar comparative results when used in direct pulp protection after pulpotomy.
Keywords: aluminum derivative; calcium derivative; mineral trioxide aggregate; oxide; silicate; silicate cement; tooth cement; animal; comparative study; dog; drug combination; endodontics; growth, development and aging; methodology; nonparametric test; tooth pulp disease; wound healing; Aluminum Compounds; Animals; Calcium Compounds; Dental Cements; Dental Pulp Capping; Dentin, Secondary; Dogs; Drug Combinations; Oxides; Pulpotomy; Silicate Cement; Silicates; Statistics, Nonparametric; Wound Healing